COLOR: THE PROFESSIONAL’S GUIDE UNDERSTANDING, APPRECIATING, AND MASTERING COLOR IN ART AND DESIGN - Wirania Swasty (Fakultas Seni Rupa dan Desain ITB, 2018)
Color is one of design elements which plays a significant role and influences people’s daily cultural and personal experiences. It is a subject that should be studied from multidisciplinary perspectives; not only art and design perspective, but also chemistry, physics, psychological, sociological and cultural perspectives. Color: The Professional’s Guide is a book dedicated to discussing different color topics by providing strong foundation in a holistic approach. Author is a designer and educator in color design and visual merchandising at Rhode Island School of Design Certificate Programs. She has written for many design magazine and newspaper on color and design topic. The book contains 19 chapters and organized into six parts. Color: The Professional’s Guide is, therefore, a complete guide to understand, appreciate and master color in art and design.